INSTRUCTIONAL ASPECTS AND TEST DESIGN FOR MEASURING TEACHING ABILITY IN CONTENT-BASED INSTRUCTION: A CASE STUDY AT MA CHUNG UNIVERSITY - Patrisius Istiarto Djiwandono; Daniel Ginting; Yudi Setyaningsih (Universitas Katolik Indonesia Atma Jaya, 2010)
Content-Based Instruction (CBI) is a fertile research area which calls for more intensive studies, especially in a country where English is a foreign language. Aiming at describing a typical profile of an initial stage of CBI in a private university, this paper reports a descriptive research that identifies instructional aspects of a CBI class, and sketches a preliminary specification of a test for measuring teaching ability in CBI. Qualitative data were collected through observation of the lecture sessions, open-ended questionnaires, and interviews with the students. A vocabulary profile analysis was also done to the lecture materials. The results were used as a basis for the test specification, which was later submitted to experts who judged the contents of the test. Important aspects that emerged from the data concerned linguistic performances, task, lecturer’s assistance, and learning obstacles. Accordingly, the test specification puts special emphases on delivery technique, amount of assistance, quality of tasks and rapport with the students. Keywords: Content-based instruction, test specification,teaching ability.